2009
DOI: 10.1111/j.1540-8159.2009.02333.x
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker‐Based Analysis of Atrioventricular Conduction and Atrial Tachyarrhythmias in Patients with Primary Sinus Node Dysfunction

Abstract: Potentially relevant AV block occurs frequently in patients with SND. Nonetheless, the RVP prevalence is kept low through the AAISafeR mode. The protection of SND patients with demand-actuated ventricular pacing appears reasonable. The AT prevalence is low in SND patients treated by the AAISafeR mode. Even low RVP proportions appear to favor AT. Prospective evaluation is needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
(62 reference statements)
0
4
0
Order By: Relevance
“…Such a hypothesis may explain the correlations between the AV prolongation and AF progression observed in some large studies [12,19]. Moreover, it neatly explains why more sophisticated algorithms of avoiding right ventricular pacing fail to show the clear benefit of further RVp% reduction in terms of AF development [15,20,21]. The benefit of right ventricular pacing avoidance would be compensated in those cases by the detrimental effect of a too long AV delay and greater advancement of the degenerative disease concerning the atria and both nodes in which AV prolongation would be a sign rather than a cause.…”
Section: The Incidence Of Af and Its Symptoms During The Follow-up Pementioning
confidence: 92%
See 1 more Smart Citation
“…Such a hypothesis may explain the correlations between the AV prolongation and AF progression observed in some large studies [12,19]. Moreover, it neatly explains why more sophisticated algorithms of avoiding right ventricular pacing fail to show the clear benefit of further RVp% reduction in terms of AF development [15,20,21]. The benefit of right ventricular pacing avoidance would be compensated in those cases by the detrimental effect of a too long AV delay and greater advancement of the degenerative disease concerning the atria and both nodes in which AV prolongation would be a sign rather than a cause.…”
Section: The Incidence Of Af and Its Symptoms During The Follow-up Pementioning
confidence: 92%
“…It has been shown that in those patients the incidence of AF may have different patterns beginning from non-progressive, chronic progressive or relapsing-remitting paroxysmal AF [13], and the AF pattern has not been related to any of the clinical features examined. Because there are some links between the incidence of AV block and sinus node disease like the elevated risk of AV block in patients with sinus node disease [14,15] or potentially the same genetic factors [16] and there exist such correlations between the sinus node disease and the AF [17,18], it is possible that the RVp% changes in the presented study may reflect the advancement…”
Section: Echocardiographic Indices and Afbmentioning
confidence: 96%
“…The SafeR pacing mode also counts all detected AVB episodes and provides an accurate categorization of the kind of AVB. 13 A more comprehensive description of the SafeR pacing mode can be found elsewhere. 10 , 14 …”
Section: Methodsmentioning
confidence: 99%
“…As PR evolves according to patients' activity, the AVB I degree criterion can be programmed either to rest+exercise (the device will switch to DDD during rest and exercise phases) or to exercise only (the device will switch to DDD during exercise phase only). Stockburger et al 38 reported the validation of the SafeR algorithm for all types of AVB and its safety profile in both SND and AVB populations. 13 The management of long PR seems particularly relevant as recent analyses on the ANSWER database showed that 25% of patients with SND and 48% of patients with AVB had a long PR at baseline (>230 ms), responsible for a high proportion of AVB I degree switches, and that patients with long PR (≥230 ms) were 1.68 more likely to develop persistent AF (HR, 1.68; 95% confidence interval, 1.06-2.65; P=0.027).…”
Section: Do All Ventricular Pacing Minimization Algorithms Behave Thementioning
confidence: 99%